دور الجمعیات المهنیة للمکتبات والمعلومات فى تطویر مهارات الاخصائیین بالوطن العربى : دراسة تحلیلیة - د.هبة أحمد المتبولى (المجلة الدولية لعلوم المكتبات والمعلومات)
Interaction between organizations in the field of libraries and informationin supporting and developing the skills of specialists in the Arab world. It aims toprovide a theoretical framework on the professional community and developmentof specialists in the field of libraries and information, analyze the role played byprofessional associations in the field of libraries and information, Training,knowledge and comprehensiveness of their skills, identifying strengths,weaknesses, opportunities and improvement of professional work skills toimprove and identify future plans of professional associations and associations interms of performance of their tasks and the value of their objectives, The study isbased on a number of (14) general societies in the field of libraries andinformation, in addition to the knowledge of a number of results. The mostimportant of these are the fact that all professional societies in the field of librariesand information provide training courses in the field of libraries and socialinformation (Face book) The Association of Jordanian Libraries in the field oflibraries and information in the provision of training courses and workshops thatcontribute to the development of specialists' skills, followed by the EgyptianSociety and the Arab Federation of Libraries and Information.